The Effects Of Mahogany Leaf Extract (Swietenia mahagoni (L.) Jacq) On Effects The Histological Structure Of The Gastric Mucosa In Mice (Mus musculus L.) - Tegar Adi, Wibowo; Arum, Setiawan; Sarno, S (BIOVALENTIA: Biological Research Journal, 2025)
Each part of the mahogany plant (Swietenia mahagoni (L.) Jacq) has many benefits that can help cure diseases traditionally. Phytochemical screening of mahogany plants has isolated more than 45 limonoids, and it is known that they contain fatty acids and terpenoids.This experiment was performed to examine the effect of mahogany leaf extract (S.mahagoni (L.) Jacq.) on the histological structure of the gastric mucosa in mice (Mus musculus L.) and prove the effect of giving leaf extract in reducing peptic ulcer scrores ini mice. Twenty mice were divided into 5 treatment groups. Before giving mahogany leaf extract, the mice underwent acclimatization and fasted for 2 x 48 hours. The administration of mahogany leaf extraxt is carried ot orally using a probe with repetitions 3 times every 8 hours. The doses of mahogany eaf extract given are 500mg/kgBB, 1.000 mg/kgBB, and 2.000 mg/kgBB. The other groups were negative control dan positive control. After the treatmen of the mice was somplete, the mice were dissected to remove their stomachs and carried out observations. The gastric mukosa was observed by scoring based on the severity of the ulcer and the hematoxylin eosin staining showed that mahogany leaf methanol extract had a better effect on the histologica structure of the mucosa in mice by reducing inflammatory cells ini the mucosal layer. Administration of mahogany leaf methanol extract had an effect in reducing peptic ulcer scores in the stomachs of mice. The higher the dose of mahogany leaf extract, the lower the degree of damage to the microscopic appearance of the mice’s gastric mucosa.